Design and engineering methods for open-rotor nacelle shaping - Zanenga, Erminio Samuele (Cranfield University, 2010)
Due to the growing transport needs in emerging economies and recent success of the low-cost airlines, the demand for short/medium-haul aeroplanes is increasing. Within the next twenty years, the existing single-aisle aircraft are likely to be replaced by new models mounting new propulsion systems. One promising con- figuration being considered is the open-rotor, which is a revision of the propfan. However, further progress has to be done in order to transform propfan engines, whose technology dates back to the 1980s, into viable and feasible open-rotor con- cepts. Among the aspects yet to be investigated in su ficient depth is the de finition of a methodology for the open-rotor nacelle design. The aim of the present research is to help enhance the knowledge in this area. Even if there are a number of important fields of investigation for open-rotor designs, this work is limited to the analysis of the pusher architecture with no exhaust impingement through rotors. The research is initially performed combining both a graphical and a compu- tational approach, investigating the mathematical and physical aspects involved in the de finition of appropriate nacelle pro files, boundary conditions for the CFD analysis and simplifi ed rotor modelling. The first simulations are mainly focused on a typical propfan nacelle, which is taken as a reference model: the computations provide useful results for evaluating its aerodynamic features ... [cont.].